(x^2-4x+6)^2-4x(x^2-4x+6) +3x^2

Question

(x^2-4x+6)^2-4x(x^2-4x+6) +3x^2

in progress 0
Gerda 2 years 2020-10-30T01:22:37+00:00 2 Answers 55 views 0

Answers ( )

    0
    2020-10-30T01:23:55+00:00

    `(x^2-4x+6)^2-4x(x^2-4x+6)+3x^2`

    `=(x^2-4x+6)(x^2-4x+6)-4x(x^2-4x+6)+3x^2`

    `=(x^2-4x+6)[-4x+(x^2-4x+6)]+3x^2`

    `=(x^2-4x+6)(-4x+x^2-4x+6)+3x^2`

    `=x^2(-4x+x^2-4x+6)-4x(-4x+x^2-4x+6)+6(-4x+x^2-4x+6)+3x^2`

    `=-4x^3+x^4-4x^3+6x^2+24x-4x^2+16x-24x-24x+6x^2-24x+12+3x^2`

    `=(-4x^3-4x^3)-x^4+(6x^2-4x^2+6x^2+3x^2)+(24x+16x-24x-24x-24x)+12`

    `=-8x^3-x^4+11x^2-32x+12x`

    0
    2020-10-30T01:24:13+00:00

    Đáp án:

    Giải thích các bước giải:

    $\text{Với đề bài phân tích đa thức thành nhân tử:}$

    $(x^2-4x+6)^2-4x(x^2-4x+6)+3x^2$

    $=(x^2-4x+6)-4x(x^2-4x+6)+4x^2-x^2$

    $=(x^2-4x+6-2x)^2-x^2$

    $=(x^2-6x+6)^2-x^2$

    $=(x^2-6x+6-x)(x^2-6x+6+x)$

    $=(x^2-7x+6)(x^2-5x+6)$ $(1)$

    $\text{Với đề bài rút gọn:}$

    $(1)=x^4-7x^3+6x^2-5x^3+35x^2-42x+6x^2-30x+36$

    $=x^4-12x^3+47x^2-72x+36$

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )